2008
DOI: 10.1002/ajmg.b.30811
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter polymorphism modulates oculomotor function and DAT1 mRNA expression in schizophrenia

Abstract: Smooth pursuit eye movement (SPEM) deficit is an established schizophrenia endophenotype with a similar neurocognitive construct to working memory. Frontal eye field (FEF) neurons controlling SPEM maintain firing when visual sensory information is removed, and their firing rates directly correlate with SPEM velocity. We previously demonstrated a paradoxical association between a functional polymorphism of dopamine signaling (COMT gene) and SPEM. Recent evidence implicates the dopamine transporter gene (DAT1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 44 publications
2
25
1
Order By: Relevance
“…First, while the DAT is most strongly expressed in the striatum, it is also reliably found in extrastriatal regions (Ciliax et al, 1999;Saba et al, 2007), with evidence of genotype dependence in the frontal cortex (Wonodi et al, 2009). This observation opens up the possibility that these extrastriatal DATs may have a role in the pharmacogenetic effects observed here, especially given previous observations of SLC6A3-related differences in the activity of cortical regions during working memory, memory recognition, and response inhibition (Bertolino et al, 2006(Bertolino et al, , 2009Congdon et al, 2009).…”
Section: Pharmacogenetic Findingssupporting
confidence: 62%
“…First, while the DAT is most strongly expressed in the striatum, it is also reliably found in extrastriatal regions (Ciliax et al, 1999;Saba et al, 2007), with evidence of genotype dependence in the frontal cortex (Wonodi et al, 2009). This observation opens up the possibility that these extrastriatal DATs may have a role in the pharmacogenetic effects observed here, especially given previous observations of SLC6A3-related differences in the activity of cortical regions during working memory, memory recognition, and response inhibition (Bertolino et al, 2006(Bertolino et al, , 2009Congdon et al, 2009).…”
Section: Pharmacogenetic Findingssupporting
confidence: 62%
“…This finding qualifies the only previous report on a possible association by Wonodi et al (2009). In the context of a clinical study on schizophrenia patients, they found a significant link between the polymorphism and predictive pursuit in their healthy control group.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, visually driven pursuit did not systematically vary across individuals. Previous studies that strived to investigate the role of dopamine in different pursuit processes used continuous waveform motion, providing perfectly predictable target trajectories, and blanked the target for a short period during ongoing pursuit (Thaker et al, 2004; Wonodi et al, 2009). Although this approach has yielded seminal insights into pursuit deficits in schizophrenia patients, we suggest that using two separate paradigms for visually guided and anticipatory pursuit allows a more detailed differentiation between underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We genotyped rs2275163C>T and rs1053230C>T (Table 2), using TaqMan technology as previously described (Wonodi et al, 2009). …”
Section: Methodsmentioning
confidence: 99%